Ekonomi Syari’ah Versus Ekonomi Konvensional - Suwadji (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
What distinguishes an economy mode sharia (Islamic economics) with conventional economics? At first glance may be indifferent, but if explored further, there is a fundamental difference between the two. To find out will it be able to begin by comparing the basic principles of both, roughly where the similarities and differences.